KLASIFIKASI MINAT SISWA UNTUK PROGRAM STUDI JURUSAN TEKNOLOGI INFORMASI - POLITEKNIK NEGERI SAMARINDA MENGGUNAKAN METODE FUZZY C-MEANS CLUSTERING - Bedi Suprapty; Fariyanti Fariyanti (J-Icon : Jurnal Komputer dan Informatika, 2020)
Students who have graduated from high school or high school will continue to a higher level such as Samarinda State Polytechnic. Samarinda State Polytechnic consists of several Departments approved by the Information Technology department. The Information Technology Department has 4 Study Programs including; D3 Informatics Engineering, D3 Computer Engineering, D4 Multimedia Information Technology and D4 Computer Technology Engineering. This research was conducted by classifying specialization of students who would continue their studies to the Department of Information Technology, Samarinda State Polytechnic. Sources of data obtained from the questionnaire. Data collection was carried out by questionnaire method, the questionnaire consisted of 15 questions and had 5 criteria. Each criterion has 3 questions. The questionnaire was distributed to 160 high school and vocational high school students in the city of Samarinda, East Kalimantan. Clusters in this study are divided into 4, namely cluster 1, an interest in the D3 Study Program in Informatics Engineering, cluster 2 an interest in the D3 Study Program in Computer Engineering, cluster 3 an interest in the D4 Study Program in Multimedia Information Technology and cluster 4 an interest in D4 in Computer Engineering Technology. Fuzzy C-means method is used in resolving these complications where the results of clustering cluster 1 consists of 41 students, cluster 2 consists of 46 students, cluster 3 consists of 21 students, cluster 4 consists of 52 students. The average MAPE percentage for the whole cluster is 27.07%.